SUPPLY CHAIN RISK ANALYSIS IN WHOLESALE PHARMACEUTICAL TRADING COMPANIES USING THE HOUSE OF RISK (HOR) METHOD - Reynaldi Junus; Imam Baihaqi (Institut Teknologi Adhi Tama Surabaya, 2025)
The Pharmaceutical Wholesaler is a legally established company authorized to procure, store, and distribute medicines in large quantities. Numerous issues within Pharmaceutical Wholesalers and their impact on business continuity highlight the need for a structured risk management system to identify and mitigate potential risks in the future. Structured risk management is a crucial component for ensuring the operational sustainability of Pharmaceutical Wholesalers, aiming to identify, analyze, and mitigate risks that may disrupt the supply chain process. This study employs the House of Risk (HOR) method to analyze risks using the SCOR (Supply Chain Operation Reference) framework, which includes the processes of Plan, Source, Make, Deliver, and Return. HOR Stage 1 identifies risk events (RE) and risk agents (RA) and calculates the Aggregate Risk Potential (ARP) value to prioritize risk agents. HOR Stage 2 designs mitigation strategies by considering the effectiveness of preventive actions and the difficulty of implementation. Based on the analysis in HOR Stage 1 through interviews and discussions, scoring was conducted for each risk event, identifying 44 risk events and 13 risk agents. Using a Pareto diagram, 7 major risk causes were identified as priorities for prevention. HOR Stage 2 evaluation resulted in nine preventive actions, with five prioritized actions recommended to control potential risks. These include forming a dedicated monitoring and updating team, developing a clear SOP-based work system, creating supplier diversification strategies, providing regular training, and conducting regular audits or evaluations.